Struktur, Kategori, dan Fungsi Sosial Pertanyaan Tradisional (Riddles) Masyarakat Kenagarian Parit Kecamatan Koto Balingka Kabupaten Pasaman Barat - Mawaddah, Abni; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2023)
As time goes by, the existence of oral literature, namely traditional questions (riddles), is now almost extinct due to increasingly sophisticated technology. If this continues, the consequences will threaten the existence of traditional questions (riddles) in society. The aim of this research is to describe: (a) the structure of traditional questions (riddles) of the Kenagarian Parit community, Koto Balingka District, West Pasaman Regency, (b) categories of traditional questions (riddles), and (c) the social function of traditional questions (riddles). This study employs descriptive qualitative research methods. In order to obtain this data, we first conducted a literature review, then conducted a field research, and finally conducted interviews with key informants in two phases (recording and transcription). There were three phases to the analytical process: (1) data classification; (2) results discussion and conclusion; and (3) reporting. Forty conventional questions (riddles) were asked of three informants to collect data for this study. Researchers in the Kenagarian Parit community in Koto Balingka District, West Pasaman Regency came to the following conclusions based on their findings: (1) the structure of traditional questions (riddles), including traditional questions (riddles) that do not conflict and traditional questions (riddles) that do. (2) Human-related, animal-related, plant-related, inanimate object-related, color-related, and riddle-related are the categories for conventional inquiries (riddles). (3) The social function of traditional questions (riddles) has two functions, namely testing someone's intelligence and as entertainment.